Overview of MIMO Technology in LTE, LTE-A & LTE-A-Pro (International Journal of Engineering and Computer Science, 2018)
The MIMO systems having large number of base station antennas often called massive MIMO or FD-MIMO have received much attention in academia and industry to provide High spectral efficiency, High energy efficiency, High hardware efficiency and processing complexity for future cellular systems such as 4G LTE systems, LTE-Advance, LTE-Advance Pro and Fifth generation cellular communication systems. This paper presents an overview of MIMO technology being applied in LTE and LTE-Advance.